The NAS System: Nursing Activities Score in mobile technology - Catalan, Vanessa Menezes; Silveira, Denise Tolfo; Neutzling, Agnes Ludwig; Martinato, Luísa Helena Machado; Borges, Gilberto Cabral de Mello (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to present the computerized structure that enables the use of the Nursing Activities Score (NAS) in mobile technology. It is a project for the development of technology production based on software engineering, founded on the theory of systems development life cycle. The NAS system was built in two modules: the search module, which is accessed using a personal computer (PC), and Data Collection module, which is accessed through a mobile device (Smartphone). The NAS system was constructed to allow other forms, in addition to the NAS tool, to be included in the future. Thus, it is understood that the development of the NAS will bring nurses closer to mobile technology and facilitate their accessibility to the data of the instrument relating to patients, thus assisting in decision-making and in staffing to provide nursing care.